(untitled) (Texas Journal of Agriculture and Biological Sciences, 2025)
This article investigates the ecological balance between pathogenic and beneficial microorganisms in the potato (Solanum tuberosum L.) root system. Based on literature analysis and experimental observations, the interactions between root-associated pathogens and beneficial fungi and bacteria are examined, highlighting their influence on plant health, disease suppression, and productivity. The study demonstrates that maintaining microbial equilibrium is essential for sustainable agriculture, improving crop resistance, and optimizing potato yield. These findings are of high scientific and practical significance for integrated crop management and microbial ecology studies.